Enhanced peroxidase‐like activity of MMT‐supported cuprous oxide nanocomposites toward rapid colorimetric estimation of H2O2. (21st December 2018) - Lian, Siming; Gao, Linna; Chen, Miaomiao; Liu, Zhenxue; Qiu, Jun; Zhang, Xiao; Luo, Xiliang; Zeng, Rongchang; Liu, Qingyun
Abstract : Nanocomposites based on Cu2 O and Ca‐montmorillonite (Ca + ‐MMT) with different composition were successfully prepared via a simple hydrothermal method. The as‐prepared Cu2 O‐MMT nanocomposites can rapidly catalytically oxidize the colorless chromogenic substrate, 3, 3′, 5, 5′‐tetramethylbenzydine (TMB) into blue oxTMB with the aid of the H2 O2 only in 30 s, which were observed by the naked eye. The reaction catalyzed by the Cu2 O‐MMT nanocomposites followed the Michaelis–Menten kinetics. Compared to the MMT or Cu2 O alone, Cu2 O‐MMT with different mass ratio exhibited an enhanced peroxidase‐like activity. The fabricated H2 O2 sensor exhibited a good response to H2 O2 with a linear detection range from 3 to 80 μM as well as a detection limit of 2.395 μM. Taking the advantages of the Cu2 O‐MMT nanocomposites, including outstanding peroxidase‐like activity and high sensitivity for colorimetric detection of H2 O2, a colorimetric sensor based on the Cu2 O‐MMT nanocomposites was designed and used to rapidly detect H2 O2 in a short time. Abstract : Cu2 O‐MMT nanocomposites can catalytically TMB into blue oxTMB with H2 O2 only in 30 s, which were observed by the naked eye. The fabricated H2 O2 sensor exhibited a good response to H2 O2 with a detection limit of 2.395 μM.